ANALISIS SISTEM INFORMASI MANAJEMEN PADA E-COMMERCE SHOPEE - Nina Liviana; Rachel Ariana Salsabila; Ravashya Adinda Nabila Wirajaya; Neng Salsabilla Siti Fadillah; Bunga Hilmi Asabella (Media Riset Bisnis Manajemen Akuntansi, 2026)
Data management and information-based decision-making. The method used was a qualitative literature study reviewing previous research findings. The analysis shows that Shopee's SIM has helped improve transaction efficiency, logistics management, and customer service. However, improvements in data security and system integration are still needed to ensure Shopee remains competitive.Keywords : Management Information System, E-Commerce, Shopee, Operational Efficiency.